COVID-19 and its long-term impact on the cardiovascular system. (4th March 2023) - Philip, Bejoy; Mukherjee, Prerona; Khare, Yuti; Ramesh, Pranav; Zaidi, Sara; Sabry, Haytham; Harky, Amer
ABSTRACT: Introduction: TheSARS-CoV-2 virus caused a pandemic affecting healthcare deliveryglobally. Despite the presentation of COVID-19 infection beingfrequently dominated by respiratory symptoms; it is now notorious tohave potentially serious cardiovascular sequelae. This articleexplores current data to provide a comprehensive overview of thepathophysiology, cardiovascular risk factors, and implications ofCOVID-19. Areas covered: Inherentstructure of SARS-CoV-2, and its interaction with both ACE-2 andnon-ACE-2 mediated pathways have been implicated in the developmentof cardiovascular manifestations, progressively resulting in acuterespiratory distress syndrome, multiorgan failure, cytokine releasesyndrome, and subsequent myocardial damage. The interplay betweenexisting and de novo cardiac complications must be noted. Forindividuals taking cardiovascular medications, pharmacologicinteractions are a crucial component. Short-term cardiovascularimpacts include arrhythmia, myocarditis, pericarditis, heart failure, and thromboembolism, whereas long-term impacts include diabetes andhypertension. To identify suitable studies, a PubMed literaturesearch was performed including key words such as 'Covid 19, ''Cardiovascular disease, ' 'Long covid, ' etc. Expert opinion: Moresophisticated planning and effective management for cardiologyhealthcare provision is crucial, especially for accommodatingchallenges associated with Long-COVID. With the potential applicationof AI and automated data, there are many avenues and sequelae thatcan be approached for investigation. Plain Language Summary: Deemed the pandemic of the century, COVID-19 is an illness affecting multiple organ systems. Although the virus is best known for its lung-related complications, its adverse effects on the heart and blood vessels are now becoming more apparent. Rapidly mutating and evolving, its unique structure enables it to undergo interactions with various proteins in the body, resulting in complications of both the heart itself and blood vessels throughout the body. Numerous risk factors have been identified to facilitate these manifestations, including existing heart disease, medication usage, and age. Research has shown that certain drug interactions induce disturbances of the heart rhythm and function. In addition to this, they can also exacerbate preexisting heart-related complications, resulting in severe manifestations. The effects on the heart and blood vessels can be divided into acute and chronic complications. Acute complications include heart failure, rhythm disturbances, heart muscle weakness, and inflammation. In addition to this, chronic complications such as high blood pressure and the new onset of diabetes could also be a consequence. Further research is necessary to improve and enhance both our understanding of the virus and our ability to anticipate heart-related symptoms early on.